KOMPENSASI, DISIPLIN KERJA, DAN KINERJA KARYAWAN - Nur Azis (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2021)
Abstract- This study aims to find out whether there is an influence of compensation and work discipline on employee performance at the An-Nur Pasirnangka Islamic Education Foundation, Tigaraksa District, Tangerang Banten Regency. Performance is the result of work that has a strong relationship with the aim of contributing to the progress of the company. Work discipline is very necessary both the individual concerned and by the company because work discipline shows a condition or attitude of respect that exists in employees towards company regulations and provisions. The data used in this study are primary and secondary data that are quantitative in nature with a sample used by 60 respondents. The analysis used is the analysis of multiple linear regression models, test classical assumptions and test hypotheses using softwere spss version 23. The results showed that the compensation t test of the calculated T value of 3.142 > T of the table 1.672 with a significant value of 0.003 < 0.05 which means that H1 is accepted, the work discipline of the calculated T value is 7.134 > T table is 1.672 with a significant value of 0.000 < 0.05 which means that H2 is accepted. It can be seen from the coefficient of determination that together compensation and work discipline for employee performance were 67.8% while the remaining 32% was influenced by other variables outside the variables used in this study.